Analysis of grape fruits and grape seed for their major , minor and trace elemental contact by XRF technique (Baghdad Science Journal, 2011)
Grapes and grape seeds are important samples employed for environmental medical studies . The air of this work was to identify and concentration calculation of the elements in grapes fruit and thier seeds by using X-Ray fluoresces technique (XRF) . Samples were collected from Abo Ghraib of Baghdad city ,the grape seeds were obtained from those samples . Both samples were taken under experimental procedure to obtain the sample which were ready for analysis . The samples were then submitted to experimental conditions using a radiation source and then samples were applied for counting analysis shows the elements Na , Mg , Al , Si , P , S , Cl , K , Ca , and Sr as major components of the samples. Fe , Sr , I , Ba and V were found an minor elements other elements Cr , Cu , Sn , Sb , Te gave a value of 5 – 10 ppm , Co , Ni , Rb , Ag ,Cd < 5 ppm for the samples of grape seeds . The analysis of grape seeds present Sr , Ca , K , Cl , S , Si , P as major components of the samples, and gave a values for Cr and Rb , Sn , Sb and Te (5 – 10 ppm) , while Co , Rb , Ni , Ag ,Cd (Less than 5 ppm) .